Editorial: Special Issue “Edge and Fog Computing for Internet of Things Systems” - Behnam Dezfouli; Yuhong Liu (Sensors, 2022)
Employing edge and fog computing for building IoT systems is essential, especially because of the massive number of data generated by sensing devices, the delay requirements of IoT applications, the high burden of data processing on cloud platforms, and the need to take immediate actions against security threats.